Dynamic modelling, simulation and basic control of CO2 absorption based on high pressure pilot plant for natural gas treatment - Salvinder, K.M.S. (Elsevier Ltd, 2018)
The continuous exploration of new gas reserves along with the increase in the global power demand necessitates the development of less demanding technologies, especially in terms of energy minimization. However, the development of CO2-rich type of gas resources poses significant challenges in the sour gas treatment industry due to bulk CO2 contaminants and high overflowing pressure at the well- head. For the treatment of CO2 rich natural gas, reliable data at high CO2 partial pressure condition is very crucial and the insight of the transient conditions must be thoroughly studied to design a controlled process that can handle any disturbances that might arise in the future. This paper reports the dynamic modelling and basic regulatory control studies of a high-pressure absorption pilot plant, which is located at Universiti Teknologi PETRONAS (UTP), for CO2 removal using MEA solvent. Steady state simulation has been demonstrated using Aspen Plus utilizing both equilibrium and rate based approaches. Dynamic and control analysis is then carried out in Aspen Dynamic using a modified equilibrium stage model. Â© 2017 Elsevier Ltd